Ectopic production of methionine enkephalin and beta-endorphin. Issue 6216 (15th March 1980) - Pullan, P T; Clement-Jones, V; Corder, R; Lowry, P J; Rees, G M; Rees, L H; Besser, G M; Macedo, M M; Galvao-Teles, A
Abstract : Immunoreactive methionine enkephalin and beta-endorphin were sought by serial dilution of tissue extracts and assay of chromatographic fractions in non-endocrine tumour tissue from three patients with the ectopic adrenocorticotrophin syndrome associated with carcinoid tumours and in normal lung tissue and thymic tissue from a patient with myasthenia gravis. In all cases serial dilution of extracts showed parellelism to standard radioimmunoassay curves. The two peptides were found in high concentration in the three tumours but were undetectable in the control tissues. In a single case tested the methionine enkephalin concentration in a vein draining the tumour was twice that in a peripheral vein. In view of their profound effect on behaviour in animals and potent analgesic activity in animals and man the ectopic secretion of methionine enkephalin and beta-endorphin may modify the clinical features of a wide variety of tumours and produce some of the diverse clinical syndromes associated with malignancy.